Effect of different durations of exposure to food-grade organic lactic acid on the growth of S. aureus and E. coli in meat from Persian sheep (Afshari breed) stored at refrigeration temperature - Mohammad Ali Mogharei; Hamed Ahari; Ali Akbar Safekordi; Shabnam Haghighat Khajavi (Czech Journal of Food Sciences, 2018)
The effect of lactic acid in extending the shelf life of sheep carcasses stored at 4°C was evaluated. Carcasses were assigned to four testing groups: T1 (control group), T2 (1% lactic acid spray), T3 (2% lactic acid spray) and T4 (3% lactic acid spray). There were statistically significant differences among the groups in the colour score for each minced meat sample at 48, 72, and 96 h (X2 = 9.9, P = 0.019; X2 = 9.7, P = 0.021, respectively). The minimum mean rank of the odour score was found using 1% lactic acid at 72 h (3.0), which was significantly different (P < 0.05) when compared to the other groups. The MANOVA test showed no significant difference (P > 0.05) in the percentage of protein during the days of the experiment. The interaction effect between the sampling time and acid concentration levels on the measurement of S. aureus log10 CFU showed that the marginal mean of that measurement was significant (P < 0.05) at 48, 72, and 96 hours. The minimum value for E. coli log10 CFU was observed at the time point of 96 h in groups 2 and 4 (3.3 ± 0.03) with no significant difference (P > 0.05) between them. In conclusion, 1% lactic acid is more effective in extending the shelf life of sheep meat in comparison to 2 and 3% lactic acid.